Topography of Si epitaxial monolayers obtained on Si (001) substrate by computer simulations - Pyziak, L.; Obermayr, W.; Zembrowska, K.; Kuzma, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Fractal analysis was used for the description of the geometry of the clusters formed within the Monte Carlo simulation of the first monolayer growth on Si substrate. Pulse laser deposition method was assumed for the epitaxy. Layers were obtained for various substrate temperatures varying in the range from 600 K to 800 K. The topography of plane clusters formed were characterised by their fractal box-like dimension. The relation between this dimension and the shape of the clusters was addressed.